Ferrihydrite-Chitosan Nanocomposite As A Recyclable Flocculant For Palm Oil Mill Effluent - Azlan Kamari, Nurulsaidah Abdul Rahim, Norjan Yusof (Tanjung Malim, 2024)
Ferrihydrite-Chitosan Nanocomposite As A Recyclable Flocculant For Palm Oil Mill Effluent by Azlan Kamari, Nurulsaidah Abdul Rahim, Norjan Yusof